Minimum detection limit of an in-house nested-PCR assay for herpes simplex virus and varicella zoster virus - Rodrigues,Diogenes (2013)
Introduction Herpes simplex virus (HSV) and varicella zoster virus (VZV) are responsible for a variety of human diseases, including central nervous system diseases. The use of polymerase chain reaction (PCR) techniques on cerebrospinal fluid samples has allowed the detection of viral DNA with high sensitivity and specificity. Methods Serial dilutions of quantified commercial controls of each virus were subjected to an in-house nested-PCR technique. Results The minimum detection limits for HSV and VZV were 5 and 10 copies/µL, respectively. Conclusions The detection limit of nested-PCR for HSV and VZV in this study was similar to the limits found in previous studies.